Project-Based Learning in Cultivating a Love of Batik through Hand-drawn Batik Training with Natural Dyes for Children - Bambang Robiin; Zahrul Mufrodi; Rachma Tia Evitasari; Caraka Putra Bhakti (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Batik has become a cultural heritage that has been recognized internationally by UNESCO. Indonesian batik has been known worldwide, even the president of the Republic of Indonesia has set October 2 as the national batik day. This should be a matter of pride for the people of Indonesia, especially Yogyakarta, which has a batik culture. The pride of the batik culture that has been recognized by the world must be owned by the Indonesian people as a whole. Not only to adults but also to children. Unfortunately, in this globalization and modern era, children, especially in the Semaki and Kotagede sub-districts, are more interested in modern culture than batik. The development of technology has given a considerable influence on children in the current era of globalization. Children are more interested in playing gadgets than making batik. The complicated process of making batik becomes less attractive to the younger generation. This community service program is carried out in the form of collaborative learning with the theme Project based learning in fostering a love of batik from an early age through written batik training with natural dyes for children. The purpose of this PPM is to provide knowledge and understanding to students and children about how to make batik with natural dyes. By knowing and understanding how to make batik, it is hoped that children in the Semaki and Purbayan sub-districts will be interested in batik culture and will develop a sense of love and pride in the batik culture that has become a legacy of their ancestors. The method of this service activity consists of socialization, debriefing, natural dye testing, written batik training, natural dye training, evaluation, and reporting. This activity will be held from 21 to 26 December 2021 in Semaki and Purbayan villages. This activity has succeeded in increasing the knowledge and understanding of participants, both students and children. Students' understanding of batik skills increased from 27% to 100% while students' natural coloring skills increased from 12% to 100%. The understanding of the children also experienced a significant increase. The children's batik skills increased from 25% and 7.5% to 100% being able to make batik. While natural coloring skills increased from 4% and 0% to 100%.